2017
DOI: 10.1016/j.molcel.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

RECQ5 Helicase Cooperates with MUS81 Endonuclease in Processing Stalled Replication Forks at Common Fragile Sites during Mitosis

Abstract: The MUS81-EME1 endonuclease cleaves late replication intermediates at common fragile sites (CFSs) during early mitosis to trigger DNA-repair synthesis that ensures faithful chromosome segregation. Here, we show that these DNA transactions are promoted by RECQ5 DNA helicase in a manner dependent on its Ser727 phosphorylation by CDK1. Upon replication stress, RECQ5 associates with CFSs in early mitosis through its physical interaction with MUS81 and promotes MUS81-dependent mitotic DNA synthesis. RECQ5 depletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 39 publications
3
85
0
Order By: Relevance
“…These factors together lead to incomplete DNA replication of the region under stress conditions . The entry of cells with un‐replicated regions into mitosis triggers DNA repair synthesis to minimize chromosome mis‐segregation . The remaining un‐replicated regions are hotspots for genomic instability and chromosomal rearrangements.…”
Section: The Multifaceted Basis Underlying Fragile Site Instabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…These factors together lead to incomplete DNA replication of the region under stress conditions . The entry of cells with un‐replicated regions into mitosis triggers DNA repair synthesis to minimize chromosome mis‐segregation . The remaining un‐replicated regions are hotspots for genomic instability and chromosomal rearrangements.…”
Section: The Multifaceted Basis Underlying Fragile Site Instabilitymentioning
confidence: 99%
“…41,42 The entry of cells with un-replicated regions into mitosis triggers DNA repair synthesis to minimize chromosome missegregation. 43,44 The remaining un-replicated regions are hotspots for genomic instability and chromosomal rearrangements. This section focuses on the potential genetic and epigenetics sources of CFS instability.…”
Section: Xp21mentioning
confidence: 99%
“…If such cells proceed into mitosis, sister chromatids are interlinked as replication intermediates and can be visualized as UFBs during cytokinesis . When UFBs are properly processed by endonuclease Mus81, these under‐replicated genomic regions form visible gaps or breaks on condensed chromosomes during mitosis . Thus, difficult‐to‐replicate regions in mammalian cells are defined as chromosomal fragile sites because these regions are prone to forming gaps and breaks, particularly following DRS .…”
Section: Drs Is a Source Of Genome Instabilitymentioning
confidence: 99%
“…RECQL5 (17q25.1) encodes for three protein isoforms (α, β, γ) among which the most studied is RECQL5β that has 991 residues, ubiquitous tissue expression, and nuclear location (Bohr, ). RECQL5 is implicated in DNA replication, transcription, and repair (Kanagaraj et al, ; Paliwal, Kanagaraj, Sturzenegger, Burdova, & Janscak, ; Popuri, Tadokoro, Croteau, & Bohr, , Saponaro et al, ) and specifically involved in the regulation of the homologous recombination (HR) DNA repair pathway (Di Marco et al, ; Hu et al, ; Pellatt et al, ), in which BRCA1, BRCA2, and most of the known HBOC susceptibility genes are implicated. In addition, it has been shown that RECQL5 suppresses tumor formation, and knock‐out mice homozygote for Recql5 deletion have increased cancer predisposition (Hu et al, ; Hu, Lu, & Luo, ).…”
Section: Introductionmentioning
confidence: 99%